2018
DOI: 10.1103/physrevlett.121.087206
|View full text |Cite
|
Sign up to set email alerts
|

Early Stages of Ultrafast Spin Dynamics in a 3d Ferromagnet

Abstract: Prior to the development of pulsed lasers, one assigned a single local temperature to the lattice, the electron gas, and the spins. With the availability of ultrafast laser sources, one can now drive the temperature of these reservoirs out of equilibrium. Thus, the solid shows new internal degrees of freedom characterized by individual temperatures of the electron gas T_{e}, the lattice T_{l} and the spins T_{s}. We demonstrate an analogous behavior in the spin polarization of a ferromagnet in an ultrafast dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 34 publications
6
44
0
Order By: Relevance
“…In addition, as mentioned above, OISTR is not the only process that evolves during the time scale of the femtosecond optical excitation. For instance, it has just recently been shown that ultrafast spin excitations (28) and nonequilibrium spin polarizations (26,27) also evolve on the time scale of the optical laser pulse itself (i.e., up to about 30 fs in our case). Although these processes could potentially contribute to the dynamics that we observe, the good agreement between our TD-DFT calculations and experimental findings strongly suggests that OISTR is the dominant process here.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, as mentioned above, OISTR is not the only process that evolves during the time scale of the femtosecond optical excitation. For instance, it has just recently been shown that ultrafast spin excitations (28) and nonequilibrium spin polarizations (26,27) also evolve on the time scale of the optical laser pulse itself (i.e., up to about 30 fs in our case). Although these processes could potentially contribute to the dynamics that we observe, the good agreement between our TD-DFT calculations and experimental findings strongly suggests that OISTR is the dominant process here.…”
Section: Discussionmentioning
confidence: 73%
“…Recent work has explored ultrafast laserinduced spin dynamics in ferromagnetic alloys and multilayers, where distinct responses-such as the existence of a time lag between the quenching of the magnetization of different elements in an FeNi alloywere observed (15). Other recent work has shown that an ultrafast laser pulse can create high-energy magnons in simple ferromagnets, on time scales 10 times faster than previously suspected, within tens of femtoseconds (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the experimental detection of the presence of OISTR in a given material remains challenging, as it requires access to the element-specific transient density of states (DOS) around the Fermi energy, E F . While time-resolved photoelectron spectroscopy can access the valence band structure of magnetic solids in great detail [20][21][22][23] , it is limited to surfaces and does not provide element specificity. To gain access to ultrafast changes of element-specific magnetization, an increasing number of experiments have made use of the magnetic contrast at 3p resonances in the XUV spectral range.…”
mentioning
confidence: 99%